2012
DOI: 10.1007/s00417-012-2032-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemodialysis (HD) on intraocular pressure, ocular surface, and macular change in patients with chronic renal failure

Abstract: The changes in the ophthalmologic findings after HD were consistent and significant in all CRF subjects. These changes correlated with the increase in plasma colloid osmotic pressure. HD can correct the volume and composition of ocular fluid. Therefore, it can affect the ophthalmologic findings in a short period of time. In addition, for good examination quality, it is recommended that an ophthalmologic examination in CRF patients be performed on a non-dialysis day or prior to HD on a dialysis day. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 26 publications
11
81
1
13
Order By: Relevance
“…Birçok çalışmada, hemodiyaliz sonrası refraksiyon değişikliklerinden veya gözyaşı film tabakası ve oküler yüzey değişikliklerinden kaynaklanan DEİGK düzeylerinde azalma olduğu bildirilmiştir. 1,13 Ayrıca, hemodiyalize giren KBY hastalarında, hemodiyaliz seansında gelişen hipotansiyon ve/veya anemi nedeni ile oksijen taşıma kapasitesindeki azalmaya bağlı olarak gelişen anterior iskemik optik nöropati nedeni ile de görme keskinliğinde düşüş yaşanabileceği bilinmektedir. 18 Çalışmamızda, diyaliz sonrası optik nöropati gö-rülmedi.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Birçok çalışmada, hemodiyaliz sonrası refraksiyon değişikliklerinden veya gözyaşı film tabakası ve oküler yüzey değişikliklerinden kaynaklanan DEİGK düzeylerinde azalma olduğu bildirilmiştir. 1,13 Ayrıca, hemodiyalize giren KBY hastalarında, hemodiyaliz seansında gelişen hipotansiyon ve/veya anemi nedeni ile oksijen taşıma kapasitesindeki azalmaya bağlı olarak gelişen anterior iskemik optik nöropati nedeni ile de görme keskinliğinde düşüş yaşanabileceği bilinmektedir. 18 Çalışmamızda, diyaliz sonrası optik nöropati gö-rülmedi.…”
Section: Discussionunclassified
“…1,[9][10][11][12][13][14][15] Bu çalışmada; KBY hastalarında hemodiyaliz tedavisi öncesi ve sonrası düzeltilmiş en iyi görme keskinliği (DEİGK), GİB, koroid kalınlığı ve makuler volüm gibi değişimlerin tespit edilmesi amaç-lanmıştır.…”
unclassified
“…Because the aim of hemodialysis is to correct the abnormal distribution of bodily fluids, ocular hemodynamics are expected to be affected by this rearrangement. In one study, researchers reported several hemodialysis-related changes, including decreased visual acuity, IOP, corneal thickness, and basal tear secretion; however, the authors found no significant change in retinal thickness using SD-OCT (4) . The authors concluded that the shifting of water from the interstitial fluid into the plasma results in a drop in tear secretion, aqueous production, and corneal hydration.…”
Section: Discussionmentioning
confidence: 99%
“…1,[5][6][7][8][9][10][11] Son yıllarda kullanıma giren, Fourier prensibi ile çalışan optik koherens tomografi (OKT) cihazı ile retina ve RSLT'nin yüksek çözünürlükte kesitsel görüntülemesi yapılabilmektedir. 7,8,12,13 Diyabete bağlı maküla ödemi olan hastalarda OKT cihazı kullanılarak yapılan bir çalışmada, hemodiyalizin ödemi azaltarak retina kalınlığında incelmeye neden olduğu bildirilmiştir.…”
Section: Diyabetik Olmayan Kronik Böbrek Yetmezliği Hastalarında Hemounclassified